How do you solve (3y + 2) = ( 4y - 3)?

3 Answers
Nov 13, 2017

y=5

Explanation:

color(blue)((3y+2)=(4y-3)

First of all, take of the parenthesis

rarr3y+2=4y-3

Add 3 both sides

rarr3y+2+color(red)(3)=4ycancel(-3+color(red)(3)

rarr3y+5=4y

Subtract 3y both sides

rarrcancel(3y)+5-cancel(color(red)(3y))=4y-color(red)(3y)

rarr5=y

color(green)(rArry=5

Hope that helps!!! ☺☻

Nov 13, 2017

See a solution process below:

Explanation:

First, remove each term from their parenthesis;

3y + 2 = 4y - 3

Next, subtract color(red)(3y) and add color(blue)(3) to each side of the equation to solve for y while keeping the equation balanced:

-color(red)(3y) + 3y + 2 + color(blue)(3) = -color(red)(3y) + 4y - 3 + color(blue)(3)

0 + 5 = (-color(red)(3) + 4)y - 0

5 = 1y

5 = y

y = 5

Jan 10, 2018

See below

Explanation:

Usually i don't consider increasing my workin by subtracting something from both sides . I decrease the work by shifting variables and constants from L.H.S to R.H.S or vice-versa .
3y+2=4y-3
I took 3y to R.H.S and -3 to L.H.S by inverting their additive signs .
This becomes
2+3=4y-3y
5=y .